2020
DOI: 10.1371/journal.ppat.1008323
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of Fusarium myosin I inhibition by phenamacril

Abstract: Fusarium is a genus of filamentous fungi that includes species that cause devastating diseases in major staple crops, such as wheat, maize, rice, and barley, resulting in severe yield losses and mycotoxin contamination of infected grains. Phenamacril is a novel fungicide that is considered environmentally benign due to its exceptional specificity; it inhibits the ATPase activity of the sole class I myosin of only a subset of Fusarium species including the major plant pathogens F. graminearum, F. asiaticum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 59 publications
4
48
0
Order By: Relevance
“…In addition, our simulations indicate that myosin alone, in the absence of the inhibitor blebbistatin, can adopt a conformation during the second converter rotation that shows high similarities with the myosin conformation in our crystallized myosin-II·ADP·blebbistatin complex, with all critical structural elements, involved in chemomechanical coupling, in comparable positions. This is in good agreement with various earlier studies, which showed that other known myosin modulators trap the myosin motor in distinct conformational states of the motor cycle, inducing only smaller local structural changes [ 14 , 15 , 16 , 17 ]. The applied simulations were performed in the absence of blebbistatin and were unbiased in the way that the myosin-II·ADP·blebbistatin crystal structure was not included during our TMD simulations, but we induced the power stroke by forcing the distant converter to rotate, which eventually led to associated changes in the motor domain and particularly the active site, thereby populating a conformation that resembled our blebbistatin-bound myosin-II structure.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, our simulations indicate that myosin alone, in the absence of the inhibitor blebbistatin, can adopt a conformation during the second converter rotation that shows high similarities with the myosin conformation in our crystallized myosin-II·ADP·blebbistatin complex, with all critical structural elements, involved in chemomechanical coupling, in comparable positions. This is in good agreement with various earlier studies, which showed that other known myosin modulators trap the myosin motor in distinct conformational states of the motor cycle, inducing only smaller local structural changes [ 14 , 15 , 16 , 17 ]. The applied simulations were performed in the absence of blebbistatin and were unbiased in the way that the myosin-II·ADP·blebbistatin crystal structure was not included during our TMD simulations, but we induced the power stroke by forcing the distant converter to rotate, which eventually led to associated changes in the motor domain and particularly the active site, thereby populating a conformation that resembled our blebbistatin-bound myosin-II structure.…”
Section: Resultssupporting
confidence: 93%
“…Computational and energetic reconstruction of the ADP release pathway from the crystallographically resolved pre-power stroke state (with a strongly bound ADP) up to nucleotide dissociation from the motor domain suggests the population of low-energy conformations along the release pathway that highly resemble both the proposed strong-Mg 2+ ·ADP-bound state and the myosin conformation as seen in our blebbistatin-bound myosin-II·ADP crystal structure, without including the two experimental structures in the computations a priori. Hence, myosin alone seems to be able to adopt a similar conformation as our crystallized inhibitor-bound myosin structure, which is in good agreement with studies on various small molecule myosin inhibitors [ 14 , 15 , 17 ] and activators [ 16 ] that trap myosin in specific conformations that can be assigned as structural states of the actomyosin motor cycle. These results further corroborate the hypothesis that the overall crystallized structure in the presence of blebbistatin resembles a native myosin-II conformation along the power stroke.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Myosin I is an important target in Fusarium graminearum [ 33 ], and the complex crystal structure of phenamacril-bound myosin I in F. graminearum was solved. It was discovered that phenamacril binds in the actin-binding cleft of a new allosteric pocket ( Figure 2 C) [ 34 ].…”
Section: Pesticide Targetsmentioning
confidence: 99%